Lectures as a means of propaganda and its negative consequences (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses a lecture on the propaganda and agitation of the Soviet government in Uzbekistan, separate views of the political processes of the activities of the department of propaganda and agitation of the Soviet government, the topics of anti-religious propaganda in regional school desks, the content of lectures and reports.